Project cooperative multitask classrooms. Educating for equal opportunities. An innovative answer to diversity (Journal of Parents and Teachers, 2016)
The training center Padre Piquer with more than 1,100 students, owned by Montemadrid Foundation and managed by the Society of Jesus, stands out as an innovative school that fosters inclusive and intercultural education. Its training and educational history of almost 50 years has been highly recognized and their teaching team continues to assume new educational challenges and innovating to ensure that their students successfully complete its education, but without losing sight of the formation of citizens as with attitudes of help, listening, tolerance and generosity.
Keywords: Cooperative learning; inclusion; multitasking; digital competence; teacher training; attention to diversity.